Experiências de aprendizagem no contexto on-line: narrativas de estudantes do Projeto Ingrede - Daniela Elisa Duarte Ferreira (2012)
This study presents a research about the classroom experiences in the virtual learning environment from the learner point of view. The objective of this research is to document and describe the nature of the experiences reported in narratives by a group of eighty-three learners who were enrolled in an ESP online course, named Projeto IngRede, at UFMG. As for the theoretical framework, the study was conducted based on the Classroom Experiences framework (MICCOLI, 2010) and counted on the contributions of many researches on (a) classroom experiences (MICCOLI, 1997; PORTO, 2003; CONCEIÇÃO, 2004; CUNHA, 2005; BARATA, 2006; ARAGÃO, 2007; LIMA, 2009; BAMBIRRA, 2009; ALONSO, 2011; COELHO, 2011; SILVA E SOUZA, 2011; ZOLNIER, 2011); (b) computer assisted language learning (WARSCHAUER, 2000; LEFFA, 2005; PAIVA, 2005; PAIVA & BRAGA, 2009); and also (c) virtual learning environments (LEFFA, 2006; PAIVA, 2008; FRANCO, 2009; PAIVA & BRAGA, 2010; PAIVA, 2010a; PAIVA & BRAGA, 2011). As for the methodology, the mixed methods research was adopted to analyze and present the results. The data were collected through narratives posted on blogs in the virtual learning environment of the course during the 1st academic semester of 2011.The results show that the classroom experiences in the virtual learning environment can be of direct nature (cognitive, affective or social) and indirect nature (contextual, conceptual, personal or future), and that there is overlapping of experiences in many moments. Finally, it was observed that the classroom experiences in the virtual learning environment provide autonomy, collaboration and harmonious relationships among participants. As a contribution to the field of Applied Linguistics, this study has implications for the framework of classroom experiences, which was expanded to contemplate the specificities of the virtual learning environment.